(untitled) (Journal of Advanced Research in Social Sciences, 2020)
In the era of globalization, knowledge of foreign languages has become essential for companies looking to get into the international market. Knowledge of English only is not enough to communicate with countries where English is not the official language. Salespeople are disadvantaged if they do not speak the language or do not know the local client`s culture. Multilingualism and interculturalism are key and strategic instruments for establishing good business relationship, professional communication with foreign customers, business negotiations etc. Particularly in the EU, but also in Asia and Latin America, much attention is paid to the role of multilingualism and interculturalism in international trade. In this paper we present the first international trade activities in which multilingualism and interculturalism have an important role and the applicability of the approach of the languages for specific purposes in the companies planning to go to foreign markets.